Adult medulloblastoma in an Australian population. (August 2022) - Parakh, Sagun; Davies, Amy; Westcott, Kerryn; Roos, Daniel; Abou-Hamden, Amal; Ahern, Elizabeth; Lau, Peter K.H.; Cheruvu, Sowmya; Pranavan, Ganesalingam; Pullar, Andrew; Lynam, James; Gzell, Cecelia; et al.
Highlights: This is the largest contemporary dataset describing treatment patterns in an adult Australian population with medulloblastoma. The optimal chemotherapy regimen in the management of adult medulloblastoma remains unclear; in this study a variety of chemotherapy regimens were used in adjuvant and relapse setting with no standardised approach. The development of more accurate molecular and age-adapted treatment strategies requires establishing national and international research collaborations. Abstract: Medulloblastoma in adult patients is a rare condition with limited contemporary demographic and treatment outcome data available in an Australian population. We conducted a retrospective review of patterns of care and outcomes of adult patients diagnosed with medulloblastoma treated at major neuro-oncology centres across Australia between January 2010 and December 2019. A total of 80 patients were identified and the median follow-up after diagnosis was 59.2 (range 0.5–204) months. A variety of chemotherapy regimens were used in the adjuvant and recurrent settings. The median overall survival (mOS) was 78 months (IQR 17.5–94.8). Patients who had no residual disease post-resection or with SHH-subtype tumours had a numerically longer 5-year survival rate than those with residual disease post resection or non-SHH subtypes respectively. The median time to recurrence from diagnosis was 18.4 months. The median OS from 1st relapse was 22.1 months (95% CI 11.7–31.4) and mOS from second relapse was 10.2 months (95% CI 6.6 - NR). This is the largest dataset examining patterns of care of adult patients with medulloblastoma in an Australian population. Substantial variation existed in the chemotherapy agents used in the adjuvant and recurrent setting. As has been demonstrated in a paediatric population, trials such as the upcoming EORTC 1634-BTG/NOA-23 trial (PersoMed-1 study) which are tailoring treatments to molecular profiles are likely to improve outcome in adult medulloblastoma.